Membrane-binding mechanism of the EEA1 FYVE domain revealed by multi-scale molecular dynamics simulations - Sansom, MSP; Larsen, A; Tata, L; John, L (Public Library of Science, 2021)
Early Endosomal Antigen 1 (EEA1) is a key protein in endosomal trafficking and is implicated in both autoimmune and neurological diseases. The C-terminal FYVE domain of EEA1 binds endosomal membranes, which contain phosphatidylinositol-3-phosphate (PI(3)P). Although it is known that FYVE binds PI(3)P specifically, it has not previously been described of how FYVE attaches and binds to endosomal membranes. In this study, we employed both coarse-grained (CG) and atomistic (AT) molecular dynamics (MD) simulations to determine how FYVE binds to PI(3)P-containing membranes. CG-MD showed that the dominant membrane binding mode resembles the crystal structure of EEA1 FYVE domain in complex with inositol-1,3-diphospate (PDB ID 1JOC). FYVE, which is a homodimer, binds the membrane via a hinge mechanism, where the C-terminus of one monomer first attaches to the membrane, followed by the C-terminus of the other monomer. The estimated total binding energy is ~70 kJ/mol, of which 50–60 kJ/mol stems from specific PI(3)P-interactions. By AT-MD, we could partition the binding mode into two types: (i) adhesion by electrostatic FYVE-PI(3)P interaction, and (ii) insertion of amphipathic loops. The AT simulations also demonstrated flexibility within the FYVE homodimer between the C-terminal heads and coiled-coil stem. This leads to a dynamic model whereby the 200 nm long coiled coil attached to the FYVE domain dimer can amplify local hinge-bending motions such that the Rab5-binding domain at the other end of the coiled coil can explore an area of 0.1 μm2 in the search for a second endosome with which to interact.